Student Learning Creativity in Facing Various Learning Tasks in University - Romli, Mustain; Abidin, Munirul (Khalifah : Jurnal Pendidikan Nusantara, 2024)
The aim of this article is to provide a concrete picture of students' creative learning efforts in university.This research focuses on how creative learning is carried out by students in university when facing a large number of assignments. Using a qualitative approach with data collection methods in the form of interviews. The research object at the State Islamic University of Maulana Malik Ibrahim Malang involved six postgraduate students majoring in Islamic Education Management. The data analysis technique uses a model developed by Miles and Huberman which consists of data reduction, data presentation and data verification. Based on the research results and discussion, the data findings reveal, among others: 1. Self-management (time management and maintaining balance), 2. Intelligence (emotional intelligence and intellectual intelligence), 3. Productivity (learning motivation and learning spirituality).